Study of Effective Relationship Marketing on Service Quality Provided and Loyalty Customers (Case Study: Tehran Shahrvand Chain Stores) - Maymand, Mohammad Mahmoudi; Kazemi, Ali; Fatehi, Nazanin Sadat (International Review of Management and Marketing, 2017)
Relationship marketing is the art of business today. To maintain key customers (profitable) existing skills to create the proper relationship with the customer is essential. Research has shown that the cost of attracting new customers 5 times the cost of retaining existing customers. In this study, the effect on quality of services provided relationship marketing and loyalty customers are addressed. The populations of the study are consumers of Tehran Shahrvand chain stores. In this study, data analysis, structural equation modeling was used to describe the research. Based on the conceptual model, the relationship between relationship marketing dimensions (trust, commitment, communication, conflict handling) on the quality of services provided and loyalty customers investigated research shows that all hypothesis of research ways and have been approved. Keywords: relationship marketing, service quality, loyalty customers JEL Classifications: C32; O13; O47